Reliability and validity of the FORUM-P and FORUM-C: two novel instruments for outcome measurement in forensic mental health - Ryland, Howard (Psychology, crime & law, 2024)
We conducted a series of tests on the FORensic oUtcome Measure (FORUM), a novel tool for measuring outcomes in forensic mental health services, which consists of complementary patient-reported (FORUM-P) and clinician-reported instruments (FORUM-C). Inpatients and outpatients at a UK forensic psychiatric regional service completed the FORUM-P and members of their clinical teams completed the FORUM-C. Patients and clinicians also provided qualitative feedback on the instruments. We assessed test-retest and inter-rater reliability in standard ways. Sixty-two patients participated with a mean age of 41.0 years (standard deviation 11.3). Thirty-five clinicians provided information about these patients. For internal consistency, Cronbach’s alpha for FORUM-P was 0.87 (95% confidence interval 0.80–0.93) and for FORUM-C was 0.93 (95% confidence interval 0.91–0.96). For test-retest reliability, weighted kappa for FORUM-P was 0.44 (95% confidence interval 0.24–0.63) and for FORUM-C was 0.78 (95% confidence interval 0.73–0.85). For inter-rater reliability, Spearman correlation coefficient for overall FORUM-C score between the first rating by clinician 1 and clinician 2 was 0.47 (95% confidence interval 0.18–0.69). For comprehensiveness, comprehensibility, and relevance FORUM-P and FORUM-C were both rated as good. FORUM-P and FORUM-C provide a novel, robust set of complementary instruments with promising psychometric properties for monitoring outcomes in forensic mental health.